Mansonella ozzardi: a neglected New World filarial nematode - Lima, Nathália F. (2016)
Mansonella ozzardi (Nematoda: Onchocercidae) is an understudied filarial nematode, originally described by Patrick Manson in 1897, that can be transmitted by two families of dipteran vectors, biting midges (most of them members of the genus Culicoides) and black flies (genus Simulium). With a patchy geographic distribution from southern Mexico to northwestern Argentina, human infection with M. ozzardi is highly prevalent in some of the Caribbean islands, along riverine communities in the Amazon Basin, and on both sides of the border between Bolivia and Argentina. There is no clinical entity unequivocally associated with M. ozzardi infection, although fever, arthralgia, headache, cold lower extremities, and itchy cutaneous rashes are occasionally mentioned in case report series. More recently, ocular manifestations (especially keratitis) have been associated with mansonelliasis, opening an important area of investigation. Here, we briefly review the biology, epidemiology, pathogenesis, and clinical aspects of M. ozzardi infection and point to some existing knowledge gaps, aiming to stimulate a research agenda to help filling them.